Minaselates, a new genus and new species of Epiphragmophoridae from Brazil (Gastropoda: Stylommatophora: Helicoidea) - Cuezzo, Maria Gabriela (2016)
We describe a new genus and a new species in the family Epiphragmophoridae, Minaselates paradoxa sp. n. The new species was found at the National Park Cavernas do Peruaçu, in northern portion of the state of Minas Gerais, Brazil. Minaselates paradoxa sp. n. is classified in Epiphragmophoridae based on the fact that it shares the following diagnostic features of the family: a dart apparatus with a single dart sac, and two unequal mucous glands at the terminal genitalia. Minaselates gen. n. differs from Epiphragmophora Doering, 1874 by having a granulose protoconch, shell spire with blunt apex, complex microsculpture on the teleoconch and closed umbilicus fused with the shell wall. Also, significant differences between the two genera are the presence of a long and thin kidney that extends more than half the length of the pulmonary cavity, the presence of a flagellar caecum, and a smooth jaw in Minaselates gen. n. The finding of this new species and genus is particularly significant to refine the definition of the family, since Epiphragmophoridae has been traditionally diagnosed using the same characters of Epiphragmophora. Dinotropis Pilsbry & Cockerell, 1937, the other valid genus in the family, is monospecific and is only known by the morphology of the shell. In many ways it is similar to Epiphragmophora. A cladistics analysis was made in the present study which supports Minaselates gen. n. as a different entity and as sister group of the Epiphragmophora within Epiphragmophoridae.